AKTIVITAS PUBLIC RELATIONS MAL CIPUTRA SERAYA PEKANBARU DALAM UPAYA MENINGKATKAN CITRA PERUSAHAAN - Sylvia Monani; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
When the Ciputra Seraya Pekanbaru Mall got crisisses that are related to the accidents successively in 2012 and the issuesregarding of employees who resigned because of inconvenience to the company, the image of Ciputra Mall remains good even thus increased. Therefore, this research was conducted with the purposes are :to understand the roles and functions of public relations of Ciputra Seraya Pekanbaru Mall as one of the efforts to increase its image, to find out the activities of public relations of Ciputra Seraya Pekanbaru Mall in improving the image of the company and to detect the supporting and restricting factors of public relations activities of Ciputra Seraya Pekanbaru Mall as an attempt to improve the image ofthe company.The researcher used qualitative descriptive research method and collect the data by observation, interview and documentation toward objects of this research. In this case, they are public relation activities of Ciputra Seraya Pekanbaru Mall in improving the image of the company. The total of sample in this research is eleven informants who were selected trough purposive sampling and accidental sampling technique. The types of data in this research in the followings: (a) primary data that is the results of interview and observation; (b) secondary data which is formed as files from the company related to this research.This researchshowed thatthe roles of public relations Ciputra Mall are becoming technicians and managers, and its functions are as a communicator, relationship, backed up management, and good image maker. The activities of public relations Ciputra Mall are the internal relations, external relations, relationship marketing, media relations, promotion and special events, publicity, sponsorship, crisisses and issues management, and community relations. The implementation of public relations activities Ciputra Mall are supported by a good management, utilizing the development of science and technology (social media), creative and innovative human resources. While the restricting factors are existence of rogue tenants, the limitation of parking area and rents as well as the competitors.Keyword: activities, public relations, image, corporate